Primeiros dados quali-quantitativos do mexilhão-dourado, Limnoperna fortunei (Dunker), no Delta do Jacuí, no Lago Guaíba e na Laguna dos Patos, Rio Grande do Sul, Brasil e alguns aspectos de sua invasão no novo ambiente - Dreher Mansur, Maria Cristina (2003)
At the end of 1998 and the beginning of 1999, the golden mussel Limnoperna fortunei (Dunker, 1857), Mytilidae, originating from Southeast Asia, was registered for the first time in the Guaíba Lake Basin, Rio Grande do Sul State, Brazil. Quantitative samples were taken since the first register and for two years at various localities in the Jacuí Delta, northern limit of Guaíba Lake, and in the south limit of the later where it empties into Patos Lagoon. Samplings in Patos Lagoon revealed the presence of L. fortunei in October 2000 at Arambaré (30º54’S, 51º30’W) and in January 2001 at São Lourenço do Sul (31º20’S, 51º58’W). Quantitative samplings on roots of water hyacinths Eichhornia azurea (Sw.) Kunth and E. crassipes (Mart.) Solms-Laubach, on rhizomes of rushes Scirpus californicus (C.A. Mey.) Steud. and on trunks of Cephalanthus glabratus (Spreng.) K. Schum, were made in Jacuí Delta and on the beaches of Vila de Itapuã and Pombas camping area, in the Municipality of Viamão. Limnoperna fortunei encreased in number to a maximum density of 27,275 individuals/m2 one year and five months after the first register and 62,100 individuals/m2 two years later. In November 2000, i.e., two years after the appearance of the species in Guaíba Lake, it was recorded the first macrofouling in the pipes catching water for the city of Porto Alegre and in filters and pipelines of the cellulose industry Riocell-Klabin, Municipality of Guaíba (30º06’S, 51º20’W). Limnoperna fortunei preferentially occur on rhizomes of rushes, initially forming flat clusters that grow to large mass. It also fix on the shells and soft parts of native bivalves and on shells and operculum of gastropods, prevening full closure of these mollusks. The recent decrease of rushy areas on the shores of Guaíba Lake is attributed to invasion of L. fortunei.